Long-term anti-itch effect of botulinum neurotoxin A is associated with downregulation of TRPV1 and TRPA1 in the dorsal root ganglia in mice. Issue 9 (14th June 2017) - Cao, Lei-Fang; Si, Meng; Huang, Ya; Chen, Li-Hua; Peng, Xiao-Yan; Qin, Ya-Qin; Liu, Teng-Teng; Zhou, Yan; Liu, Tong; Luo, Wei-Feng
Abstract : Itch is a common symptom in patients with skin and systemic diseases, but the effective treatment is limited. Here, we evaluated the anti-itch effects of the botulinum toxin type A (BoNT/A) using acute and chronic dry skin itch mouse models, which were induced by compound 48/80, chloroquine, and a mixture of acetone–diethylether–water treatment, respectively. Pretreatment of intradermal BoNT/A exerted long-term inhibitory effects on compound 48/80-induced and chloroquine-induced acute itch on days 1, 3, 7, and 14, but not on day 21, in mice. Furthermore, a single injection of BoNT/A reduced the expression of the transient receptor potential cation channel, subfamily V, member 1 (TRPV1), and the transient receptor potential cation channel, subfamily A, member 1 (TRPA1) at both transcriptional and translational levels in the dorsal root ganglia (DRG) in mice. Pretreatment of BoNT/A also attenuated chronic itch induced by acetone–diethylether–water treatment and abolished the upregulation of TRPA1 in the DRG. Thus, it was suggested that downregulation of the expression of TRPA1 and TRPV1 in the DRG may contribute toward the long-term anti-itch effects of a single injection of BoNT/A in mice and BoNT/A treatment may serve as an alternative strategy for anti-itch therapy.